Modeling the workflow of bug prioritization tasks descriptively using the past events - Raja Altaf, Sohaib; Sheikh Abdul Aziz, Madihah; Shah, Asadullah (IIUM Press, 2023)
Prioritizing bugs is one of the critical decision-related tasks in managing the maintenance phase whereas it is exposed as a key challenge in handling bug reports. On the other hand, the bug triager is a prominent role to observe influencing factors for handling the bug prioritization tasks effectively. Analysis of previous bug reports shows that it is essential to handle bug prioritization tasks with the appropriate workflow. However, it is revealed that there is a research gap in modeling the workflow of prioritization tasks. The paper aims to characterize the workflow model of prioritization tasks. This research is based on a document analysis design using qualitative data from previous bug reports and other artefacts. Over 100 bug reports from large software corporations are accessed and filtered, while 20 bug reports are used for obtaining empirical data. In this study, a descriptive workflow model for prioritizing bugs is proposed by analyzing past events. This model characterizes the states of bug prioritization tasks, their statuses, and the transitions between them. Additionally, this research analyzes the industrial aspect of the proposed model and demonstrates its usefulness in providing valuable insights to the bug triager into ongoing prioritization tasks that will assist him in decision-making in prioritizing bugs retrospectively and prospectively. The finding of this research also reveals that bug reports are a valuable resource that contains significant prioritization features which is useful for illustrating the workflow of bug prioritization tasks descriptively. Thus, the implications of the model for theory and practice are discussed.